Cognitive Behavior Therapy (CBT) to Reduce Death Anxiety (Thanatophobia) in HIV/AIDS Patients - Defia Roza; Nova Yanti; Yosi Suryarinilsih; Alfitri Alfitri; Heppi Sasmita (Universitas Aisyah Pringsewu, 2022)
HIV/AIDS patients have complex problems, both physical, psychological, social, and spiritual. The most common psychological problem is thanatophobia. Psychological problems that are not resolved will reduce the patient’s immune system that it can accelerate the emergence of opportunistic infections. The purpose of this study was to determine the effectiveness of Cognitive Behavior Therapy on death anxiety. The design of this research is Mixed Method. The research was conducted at the Taratak Jiwa Hati Foundation, Padang City with a sample of 15 people who were taken by purposive sampling technique. Data collection techniques with deep interviews and the implementation of CBT in groups of five sessions for five weeks. Univariate data analysis is a frequency distribution. The bivariate analysis uses paired sample t-test. The results obtained are the average level of death anxiety of HIV patients before administering CBT is 9.6 and after giving CBT is 6.4 and n value. The mean difference between before and after CBT was 3.2 with a standard deviation of 3.55. The results of the statistical test showed that there was a significant difference between the level of death anxiety in HIV patients before and after CBT (p = 0.0 04). It is hoped that nurses will provide counseling to HIV AIDS patients to take CBT when there is a problem. It is suggested to the next researcher to conduct other research on how to overcome the mental problems of HIV patients. Abstrak: Pasien HIV/AIDS mempunyai masalah yang komplek ,baik secara fisik, psikologis , sosial dan Spiritual. Masalah psikologis yang paling sering ditemukan adalah thanatophobia. Masalah psikologis yang tidak teratasi akan menurunkan kekebalan tubuh pasien ,sehingga dapat mempercepat munculnya infeksi oportunistik. Tujuan dari penelitian ini untuk mengetahui efektifitas Cognitive Behavior Therapy terhadap kecemasan kematian . Desain penelitian ini adalah Mixed Method. Penelitian dilaksanakan di Yayasan Taratak Jiwa Hati Kota Padang dengan sampel sebanyak 15 orang yang diambil dengan teknik purposive sampling. Tehnik Pengumpulan data dengan deep interview, pelaksanaan CBT secara berkelompok sebanyak lima sesi selama 5 minggu. Analisa data univariat adalah distribusi frekuensi, Analisa bivariat menggunakan paired sample t Test. Hasil penelitian yang didapatkan adalah rata rata tingkat kecemasan kematian pasien HIV sebelum pemberian CBT adalah 9,6 dan sesudah pemberian CBT adalah 6,4 dan nilai mean perbedaan antara sebelum dan sesudah tindakan CBT adalah 3,2 dengan standar deviasi 3,55. Hasil Uji statistic didapatkan ada perbedaan yang signifikan antara tingkatan kecemasan kematian pasien HIV sebelum dan sesudah tindakan CBT (p = 0,004).Diharapkan kepada perawat untuk memberikan penyuluhan kepada Pasien HIV AIDS untuk melakukan tindakan CBT setiap ada masalah . Disarankan kepada peneliti selanjutnya untuk melakukan penelitian lain tentang cara mengatasi masalah kejiwaan pasien HIV.